Answer:
(- 1, 5 )
Step-by-step explanation:
Using the method of substitution.
Given the 2 equations
3x + 2y = 7 → (1)
x - 4y = - 21 → (2)
Rearrange (2) expressing x in terms of y by adding 4y to both sides.
x = 4y - 21 → (3)
Substitute x = 4y - 21 into (1)
3(4y - 21) + 2y = 7 ← distribute and simplify left side
12y - 63 + 2y = 7
14y - 63 = 7 ( add 63 to both sides )
14y = 70 ( divide both sides by 14 )
y = 5
Substitute y = 5 into (3)
x = (4 × 5) - 21 = 20 - 21 = - 1
Solution is (- 1, 5 )
Hello, all we need to do in this case to subtract the amount of money Bob paid for the suit from the amount of money the suit regularly costs. So:
375,95 - 268,35 = 107,6
Bob saves 107,6$.
Answer:
-0.6
Step-by-step explanation:
-2.1--0.6= 1 1/2
2 negatives make a positive
Answer:
-365
Step-by-step explanation:
-3x+7(-6-50)
- -3(-9)+7(-6-50)
- 27+7(-6-50)
- 27-42-350
- -15-350
- =-365
Answer:
x = 6
Step-by-step explanation:
Step 1: Write equation
75 - 3.5x - 4x = 4x + 6
Step 2: Solve for <em>x</em>
- Combine like terms: 75 - 7.5x = 4x + 6
- Add 7.5x on both sides: 75 = 11.5x + 6
- Subtract 6 on both sides: 69 = 11.5x
- Divide both sides by 11.5: 6 = x
- Rewrite x = 6
Step 3: Check
<em>Plug in x to verify it's a solution.</em>
75 - 3.5(6) - 4(6) = 4(6) + 6
75 - 21 - 24 = 24 + 6
54 - 24 = 30
30 = 30